Innovative Surface Designs for Sensing Applications - Saniye Soylemez; Salih Özçubukçu; Ali Cirpan (Proceedings, 2023)
An essential problem in the field of advanced sensing systems is the search for innovative surfaces that can combine an effective immobilization of biomolecules or behave directly as an enzyme mimic with increased analytical performance [...]